Single-channel magnetotactile interface with structurally decoupled polarity–eigenfrequency encoding for in-plane sliding-direction decoding - Xiaojuan Hou; Shaowei Quan; Xin Zhang; Huipeng Zhao; Lin Shi; Fen Li; Wenping Geng; Jian He; Xiujian Chou (Chemical Engineering Journal, 2026)

Observational evidence of stronger subsidence and more active photochemistry aloft associated with severe ozone pollution over rural areas - Zhuang Wang; Yujia Chen; Hao Zhang; Xianguang Ji; Xiaoyun Sun; Meng Zhang; Xinfeng Lin; Shaowei Yan; Congzi Xia; Kaidi Zhang; Xintong Chen; Yizhi Zhu; et al. (Atmospheric Research, 2026)

Influence of moisture content on failure behavior of the rock–concrete interface at positive and negative temperatures under tensile loading - Lin Luo; Xiong Liu; Ronghua Shu; Jiadong Qiu; Yingjie He; Shaowei Liu; Ziwen Zhang (Bulletin of Engineering Geology and the Environment, 2026)

Coupled surface water-groundwater-crop model considering the impact of irrigation using different calibration targets - Yuliang Zhang; Jiejie Zhang; Vijay P. Singh; Yuliang Zhou; Yi Cui; Qingxia Lin; Juliang Jin; Shaowei Ning; Zhiyong Wu; Rongxing Zhou; Jieru Yan; Shiqin Xu (Journal of Hydrology, 2026)

A meta-plasmonic biosensor for minimal protein interference profiling of serum extracellular vesicles enables high-specific discrimination of liver cancer subtypes - Jiaheng Zhu; Shaowei Lin; Baichang Deng; Jiaqing Shen; Lihuang Zeng; Qiang Niu; Tianhao Huang; Xinyue Huang; Mengqi Jiang; Wei Chen; Yinong Xie; Annuo Chen; et al. (Chemical Engineering Journal, 2026)

Placental mesenchymal stem cell–derived exosomes treat endometrial injury in a rat model of intrauterine adhesions - Lin Liang; Huidong Liu; Shaowei Wang (Molecular Genetics and Genomics, 2025)
Intrauterine adhesion (IUA) refer to persistent inflammation and fibrosis due to damaged or infected endometrium and eventually lead to dysfunction. This study aimed to explore the therapeutic effects of exosomes (Exos) derived from placental mesenchymal stem cells (PMSCs) on endometrial repair in a rat model of IUA and to elucidate the underlying molecular mechanisms. PMSCs were characterized using flow cytometry and differentiation assays (osteogenic, adipogenic, and chondrogenic). Exos were isolated via ultracentrifugation and validated through transmission electron microscopy, nanoparticle tracking analysis and Western blot. An IUA model was established via electrocoagulation, and endometrial repair was assessed using hematoxylin-eosin (HE) and Masson staining. RNA sequencing, differential expression analysis and protein-protein interaction (PPI) network construction were employed to investigate the molecular mechanisms of PMSC Exos mediated repair. The role of miR-143 in targeting MyD88 and modulating the NF-κB signaling pathway was confirmed using Dual-Luciferase Reporter Assay and qRT-PCR. PMSC Exos significantly improved endometrial thickness, increased glandular number and reduced fibrosis in the IUA model. RNA sequencing and differential expression analysis screened 3980 differentially expressed genes (DEGs) common to the IUA vs normal groups and Exo vs IUA groups. Enrichment analysis revealed significant involvement of immune system processes, natural killer cell-mediated cytotoxicity and NF-κB signaling. PMSC Exos delivered miR-143, which targeted MyD88, thereby regulating the NF-κB pathway. PMSC Exos effectively repaired endometrial damage in the IUA model by modulating the NF-κB signaling pathway through miR-143 delivery. These findings suggest that PMSC Exos hold promise as a novel therapeutic strategy for IUA, offering insights into the molecular mechanisms underlying endometrial repair.

Rapid gel preparation of layer-column structured MgAl2O4 spinel aerogel with low thermal conductivity and enhanced high-temperature stability - Xinyue Wang; Shaowei Zhang; Yingying Xing; Zichun Lin; Qing Xv; Xvke Li; Zili Huang; Hongjuan Duan; Haijun Zhang; Xingming Zhang; Ying Xu (Chemical Engineering Journal, 2025)

Organotins as inhibitors targeting human and rat steroid 5α-reductase 1: structure-activity relationship and docking analysis - Shufang Qi; Rong Cui; Wanyu Li; Jin Yang; Ke Zheng; Shaowei Wang; Ren-Shan Ge; Han Lin; Yiyan Wang (Chemico-Biological Interactions, 2025)

Association between residential greenness and coronary heart disease: A proteomics and miRNA microarray analysis - Le Yang; Qinfei Wei; Jianhui Guo; Xingyan Xu; Li Zhu; Zhiyu Zhang; Jungu Zhou; Yuting Dong; Donghong Wei; Yeying Wen; Liuyan Zheng; Shaowei Lin; et al. (International Journal of Hygiene and Environmental Health, 2025)

A multi-task learning framework for dual-polarization SAR imagery despeckling in temporal change detection scenarios - Jie Li; Shaowei Shi; Liupeng Lin; Qiangqiang Yuan; Huanfeng Shen; Liangpei Zhang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Multifunctional all-liquid microfluidic devices stabilized with molecular brush surfactants - Zhao Zhang; Weixiao Feng; Kaijuan Li; Jiaqiu Luo; Yunhui Wen; Yang Yang; Yanjun Lin; Shaowei Shi (Chemical Engineering Journal, 2025)

Associations of air pollutants and related metabolites with preterm birth during pregnancy - Liuyan Zheng; Jungu Zhou; Li Zhu; Xingyan Xu; Suping Luo; Xiaoxu Xie; Huangyuan Li; Shaowei Lin; Jinying Luo; Siying Wu (Science of The Total Environment, 2024)

Carbon-chain length determines the binding affinity and inhibitory strength of per- and polyfluoroalkyl substances on human and rat steroid 5α-reductase 1 activity - Rong Cui; Lei Ye; Xinyi Qiao; Shaowei Wang; Ke Zheng; Jin Yang; Ren-shan Ge; Han Lin; Yiyan Wang (Chemico-Biological Interactions, 2024)

Association of residential greenness, air pollution with adverse birth outcomes: Results from 61,762 mother‑neonatal pairs in project ELEFANT (2011–2021) - Yuanyuan Yu; Huishu Lin; Qisijing Liu; Yuxuan Ma; Lei Zhao; Weixia Li; Yan Zhou; Hyang-Min Byun; Penghui Li; Chen Li; Congcong Sun; Xuemei Chen; et al. (Science of The Total Environment, 2024)

Benzophenone-type ultraviolet filters inhibit human and rat placental 3β-hydroxysteroid dehydrogenases: Structure-activity relationship and in silico docking analysis - Hao Lin; Shaowei Wang; Yunbing Tang; Zhiyan Hu; Xiaofang Chen; Huitao Li; Yang Zhu; Yiyan Wang; Yi Liu; Ren-shan Ge (Toxicology Letters, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Exposure of ambient PM2.5 during gametogenesis period affects the birth outcome: Results from the project ELEFANT - Liqiong Guo; Huishu Lin; Hongyu Li; Xiaobin Jin; Lei Zhao; Penghui Li; Naiwei Xu; Song Xu; Junkai Fang; Shaowei Wu; Qisijing Liu (Environmental Research, 2023)

Intercropping with maize (Zea mays L.) enhanced the suppression of pepper (Capsicum annuum L.) Phytophthora blight by arbuscular mycorrhizal fungi - Junli Hu; Shaowei Hou; Peng Cai; Minghui Li; Zhang Cheng; Fuyong Wu; Xiangui Lin (Journal of Soils and Sediments, 2023)

Biodynamic responses of adolescent idiopathic scoliosis exposed to vibration - Shaowei Jia; Liying Lin; Hufei Yang; Junde Xie; Zefeng Liu; Tianyou Zhang; Jie Fan; Li Han (Medical & Biological Engineering & Computing, 2023)

Petrogenesis and tectonic setting of Early Silurian island-arc-type quartz diorite at the southern margin of the East Kunlun orogenic belt: analysis of the evolution of the Proto-Tethyan Ocean - Zuochen Li; Xianzhi Pei; Ruibao Li; Paul D. Bons; Lei Pei; Youxin Chen; Chengjun Liu; Meng Wang; Shaowei Zhao; Guochao Chen; Hai Zhou; Jie Zhao; et al. (International Journal of Earth Sciences, 2022)

Arbuscular mycorrhizal fungus suppresses tomato (Solanum lycopersicum Mill.) Ralstonia wilt via establishing a soil–plant integrated defense system - Minghui Li; Shaowei Hou; Junhua Wang; Junli Hu; Xiangui Lin (Journal of Soils and Sediments, 2021)

Association between particulate matter air pollution and risk of depression and suicide: a systematic review and meta-analysis - Qisijing Liu; Wanzhou Wang; Xuelin Gu; Furong Deng; Xueqin Wang; Hualiang Lin; Xinbiao Guo; Shaowei Wu (Environmental Science and Pollution Research, 2021)

Construction expression and immunogenicity of a novel trivalent outer membrane protein (OmpU‐A‐II) from three bacterial pathogens in Japanese eels ( Anguilla japonica ) - Jinping Zhao; Liqun Wu; Shaowei Zhai; Peng Lin; Songlin Guo (Journal of Fish Diseases, 2020)
Vibrio vulnificus , Edwardsiella anguillarum and Aeromonas hydrophila are three common bacterial pathogens in cultivated eels. To protect farming eels from infection by these pathogens, a trivalent outer membrane protein (OMP) containing partial sequences of OmpU from V. vulnificus , OmpA from E. anguillarum and OmpII from A. hydrophila was expressed and purified; then, the OMP was used as a vaccine to immunize Japanese eels ( Anguilla japonica ). Whole‐blood cell proliferation, antibody titres and complement and lysozyme activities were detected at different days post‐immunization (dpi), and the relative per cent survival (RPS) was determined after eels were infected with V. vulnificus , E. anguillarum or A. hydrophila at 28 dpi. The results showed that the OMP significantly stimulates the antibody titres. At 14 days after the challenge (i.e. at 28 dpi), the RPS of OMP against V. vulnificus, E. anguillarum and A. hydrophila was 20%, 70% and 11.1%, respectively. The construction, expression and immunogenicity of a trivalent Omp were reported for the first time, and this study will provide a valuable reference for the development of fish multiplex vaccines.

The better suppression of pepper Phytophthora blight by arbuscular mycorrhizal (AM) fungus than Purpureocillium lilacinum alone or combined with AM fungus - Junli Hu; Shaowei Hou; Minghui Li; Junhua Wang; Fuyong Wu; Xiangui Lin (Journal of Soils and Sediments, 2020)

Concomitant biocontrol of pepper Phytophthora blight by soil indigenous arbuscular mycorrhizal fungi via upfront film-mulching with reductive fertilizer and tobacco waste - Shaowei Hou; Yu Zhang; Minghui Li; Homgmin Liu; Fuyong Wu; Junli Hu; Xiangui Lin (Journal of Soils and Sediments, 2020)

Subcellular localization of DAXX influence ox-LDL induced apoptosis in macrophages - Guozuo Xiong; Lin Li; Shaowei Sun; Tianping Li; Duanfang Liao; Chang Shu; Qinhui Tuo (Molecular Biology Reports, 2014)